Evaluating the potential risk by probing the site-selective binding of rutin-Pr(III) complex to human serum albumin. (February 2021) - Zhu, Chunlei; Liu, Fengru; Wei, Yunlong; Zhang, Fan; Pan, Ting; Ye, Yingwang; Shen, Yizhong
Abstract: Having reported that rare earth elements displayed potential toxicity i n vivo, often be found in soil, plants and etc., which might be easily chelated with the natural functional molecule rutin to form rutin metal complexes, ultimately entering the human body by means of food chain. However, few reports paid the attention on the toxicology of the complexes consisting of rutin with rare earth ions. Here, we focused on the potential toxicity by probing the site-selective binding of the rutin-rare earth ions complexes to human serum albumin (HSA). As a proof-of-concept, we selected Pr 3+ as the representative to conjugate with rutin to form rutin-Pr(III) complex, which was further applied to interact with HSA in aqueous solution. The results exhibited that the rutin-Pr(III) complex primary bound to the hydrophobic cavity at site II (subdomain IIIA) of HSA through hydrogen bonding and van der Waals force. Through the thermomechanical analysis, we found this binding process was spontaneous because of the negative Δ G. We believe that this work may offer a new insight into understanding the physiological effects ( e.g. toxicology) of rutin and rare earth ions, which could be helpful to guide their rational use in the agriculture and environment-related industries.